REFLECTION CULTURE AS AN ASPECT OF&NBSP;SOCIAL WORKER’S PROFESSIONAL ACTIVITY - Kavaliauskienė, Vanda (Acta Paedagogica Vilnensia, 2010)
Given the changes in social life and social needs, the profession of social worker acquires new forms of expression. Increasingly greater attention is paid to the subjective aspect of professional activity. Among numerous factors that affect the professional activity of social workers, their personality traits should be emphasized. Reflection is one of them, as it takes part in the process of the subject formation and acquires specific expression. Reflection is related to learning from experience, lifelong learning, orientation to European dimensions in social life, as well as the change in the models of social life. The article covers reflection and the culture of reflection as a valuable trait of the subject of profession that accounts for a unique character of social worker. To appropriately represent the profession of social life and implement the professional activity successfully, one has to change, and the change is impossible without reflection. The change, or the renewal, is related to the ecology of the profession, which is concerned with the activity in compliance with the top criteria of the professional culture. The renewal of social worker can take place in the cognitive field (by reconsidering, processing, memorizing, and assessing professional activity-related information); in the emotional field (by (dis) satisfaction in one‘s activity and its outcomes); or in the practical field (by perceiving the actual opportunities of one‘s own impact on the objects of the activity). Reflection makes the relation of social worker with the self, as the principal tool of the profession, more outstanding and transparent; opens opportunities for creative activity, encourages search for alternative ways of activity, and upgrades the process of intervention. Reflection is necessary when creating supportive relationship, looking for ways and means to help an individual to resolve their problems, and to harmonize the relationships with the environment.